Bridging the Skill Gaps: Analyzing the Mismatch between Hospitality Education and Industry Needs in Uganda - Tushabe, Sylivia Byarugaba; Michael Murimi, Njue (African Journal of Tourism and Hospitality Management, 2025)
This is a persistent problem of skill mismatch between graduates and employers’ needs in the Ugandan hospitality industry, resulting in skill deficits that hamper employability and industry advancement. Identifying the causes of these skill gaps is the aim of this study, together with establishing recommendations to narrow the gap existing between hospitality education and the industry. The study adopted the qualitative case study research design and sampled 26 respondents from recent hospitality graduates and employers, educators or trainers, and policymakers in Kabale District, Uganda. The findings were encoded through thematic analysis. Theoretical orientation is scant with practical and interpersonal skills. Some employers also reported a concern that more attention should be paid to enhancing the practical readiness of graduates at workplaces and that there should be an increased dialog between educational institutions and employers in the hospitality sector. According to the results of the study, there is a need for a closer connection between curricula and industry demands, interconnecting the abilities needed for practical work and soft skills. Recommendations include increasing communication between teachers and supervisors from industry, enhancing internship programs, and including practical aspects. It is recommended that such collaborations be promoted through policy and funding to guarantee the appropriate match of education to the labor market requirements. These steps are relevant for reducing the existing skill gap and making graduates fit for employment opportunities in the industry.